Comparative effectiveness of bioassay methods in identifying the most virulent entomopathogenic fungal strains to control Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) - Satish Kumar Sain (Egyptian Journal of Biological Pest Control, 2019)
Abstract Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) is a serious pest of cotton that inflicts huge economic losses. Excessive use of chemical pesticides for its management causes environmental pollution and pesticide resistance. Six bioassay methods and ten entomopathogenic fungal strains (EPFs) were evaluated to find out the suitable bioassay method and the most virulent strain(s) for management of B. tabaci under laboratory and polyhouse conditions. The highest tenderness and survival period (> 30 days) of the leaves and increasing trend in nymphal mortality was recorded in a new modified polyhouse bioassay method (NMPBM). NMPBM was found to be effective, simpler, and less labor intensive for evaluating large numbers of EPF strains. Twelve newly isolated EPF strains were characterized based on their morphological and molecular characteristics. The highest whitefly nymphal mortality (at 107 conidia ml−1) was recorded by Beauveria bassiana (Bb)-4511 (95.1%), Bb-4565 (89.9%), and Metarhizium anisopliae-1299 (86.7%) at the seventh day post inoculation. However, the overall bioefficacy index was higher in Bb-4511 (78.1%), Cordyceps javanica (Cj)-102 (77.0%), and Cj-089 (75.4%) than other EPF strains. The lowest values of LC50 and LC90 were with Cj-089 and Bb-4511. The field deployment of effective formulation of these most virulent EPF strains might be helpful for managing B. tabaci populations and CLCuD incidence under insecticide resistance management programs.